The Anatomical Study of Leaves Infected with Sooty Mold on Various Plants - Salewangeng, Aswal; Sri Hastuti, Utami; Suhadi (JURNAL BIOEDUKASI, 2025)
Sooty mold is a parasitic fungus that attacks plants. Sooty mold has black mycelium that spreads and covers the surface of leaves, forming black spots. These black spots then merge, thicken, and spread to cover the entire surface of the leaves. The purpose of this study was to determine the anatomy of leaves infected with sooty mold on various plants. This study used a descriptive observational research method. The research was conducted at the Microbiology Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, State University of Malang. The results of observing the anatomical structure of leaf tissue infected by sooty mold on various plants through cross-sectioning showed that the anatomy of the leaves of the sawo kecik and mango plants indicated that the hyphae only penetrated the upper epidermal tissue, while in coffee plants, the hyphae penetrated the upper epidermal tissue, palisade tissue, spongy tissue, and lower epidermal tissue.